Science Learning by Utilizing Natural Resources at Kak Seto’s Homeschooling - Hayati, Heni Nur; Desstya, Anatri (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study is to describe the planning, implementation, and evaluation of the use of natural resources in learning science at Kak Seto's homeschool. This study used a descriptive qualitative research method with data collection techniques in the form of observation, interviews, and documentation related to natural resources and natural science learning at Kak Seto's homeschooling. The data analysis technique used is the triangulation technique, namely by reducing data, presenting data, and verifying or concluding. The results of the study found that in the planning aspect, the teacher checks and recapitulates the lesson plans once a month, and in the implementation aspect, the teacher conducts learning using contextual learning methods by utilizing natural resources in the form of wind in the windmill material. In the evaluation aspect, the teacher evaluates using LKS and communication books.